2019
DOI: 10.3389/fpsyt.2019.00553
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Alpha Connectivity During Resting-State Electroencephalography in Patients With Ultra-High Risk for Psychosis and Schizophrenia

Abstract: Schizophrenia patients always show cognitive impairment, which is proved to be related to hypo-connectivity or hyper-connectivity. Further, individuals with an ultra-high risk for psychosis also show abnormal functional connectivity-related cognitive impairment, especially in the alpha rhythm. Thus, the identification of functional networks is essential to our understanding of the disorder. We investigated the resting-state functional connectivity of the alpha rhythm measured by electroencephalography (EEG) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
3
9
1
Order By: Relevance
“…For example, the mean age of schizophrenia patients in the Andreou et al study (50) was 23.5 vs. 44.6 years in the current study. Despite this difference in theta, our finding of increased alpha connectivity at the right temporal region at scalp levels of EEG in schizophrenia patients is fully consistent with the findings of Liu et al (49).…”
Section: Discussionsupporting
confidence: 93%
“…For example, the mean age of schizophrenia patients in the Andreou et al study (50) was 23.5 vs. 44.6 years in the current study. Despite this difference in theta, our finding of increased alpha connectivity at the right temporal region at scalp levels of EEG in schizophrenia patients is fully consistent with the findings of Liu et al (49).…”
Section: Discussionsupporting
confidence: 93%
“…With regard to existing studies that focused on alphaband connectivity, most of them were examining patient populations. Of these studies one study did -in line with our findings -report increased occipital alpha connectivity in schizophrenic patients compared to healthy controls (Liu et al, 2019), which is interesting because schizophrenia often involves cognitive impairment. Other studies dealing with cognitive impairment arising from Alzheimers' disease (Ranasinghe et al, 2014;Stam et al, 2006) reported decreased alpha-band connectivity related to cognitive deficits, but more in frontal or unspecific regions.…”
Section: The Multi-spectral Character Of Positive and Negative Meg Cosupporting
confidence: 82%
“…see Sadaghiani and Wirsich, 2020). For example, more recently, it has been shown that networks of these rhythms and their network properties (such as centrality, degree, small-worldness or path length) can link spontaneous M/EEG rhythms to cognitive performance, both in healthy subjects (Langer et al, 2012;Vriend et al, 2020;Zakharov et al, 2020) or in patient populations predicting cognitive decline (Fraga Gonzalez et al, 2018;Liu et al, 2019;Ranasinghe et al, 2014;Stam et al, 2006;Stam et al, 2007;Tewarie et al, 2012) or surgery-related improvement (van Dellen et al, 2012). While offering a network view on the functional relevance of M/EEG rhythms these studies did not employ an integrated, spectrally resolved connectivity approach as we have.…”
Section: Previous Work Other Related Lines Of Research and Conceptsmentioning
confidence: 99%
“…Several studies of patients at different stages of schizophrenia, including the prodromal phases preceding the onset of the disorder, have recently reported abnormal spontaneous alpha oscillations and altered resting-state functional connectivity of the alpha rhythm [20][21][22][23] . Crucially, alpha rhythm is generated by a complex interplay between thalamic and cortical pacemakers and propagates via short and long range cortico-cortical, cortico-thalamic, and thalamo-cortical connections 24,25 .…”
mentioning
confidence: 99%
“…Moreover, according to the idea that schizophrenia originates as a disconnection syndrome 29 , first episode psychosis patients show abnormal functional connectivity, as estimated using the phase lag index (PLI), especially in the alpha rhythm. Hence, also alpha PLI, in addition to peak alpha frequency, seems to be valuable for producing clinical significance already at the onset of schizophrenia 20 . Interestingly, alpha waves propagate from anterior-to-posterior and from the cortex to the thalamus [30][31][32][33] , so that cortico-cortical and cortico-thalamo-cortical connections allow frontal regions to drive posterior alpha activity.…”
mentioning
confidence: 99%